2009
DOI: 10.1029/2008jd010869
|View full text |Cite
|
Sign up to set email alerts
|

Scenario changes in the climatology of winter midlatitude cyclone activity over eastern North America and the Northwest Atlantic

Abstract: [1] The present study explores how midlatitude winter cyclone activity can be modified under warming-induced conditions due to enhanced greenhouse gas concentrations. We performed simulations with the Canadian Regional Climate Model (CRCM version 3.5) implemented on a domain that covers the Northwest Atlantic and eastern North America. These simulations are driven by control conditions (1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 52 publications
5
30
1
Order By: Relevance
“…From studies based on the use of several reanalysis datasets with a single ETC-tracking algorithm, it is known that tracking results are also sensitive to the uncertainty in data (Hodges et al 2011). Data processing, like the interpolation of GCM outputs on a finer grid as in Long et al (2009), also influences tracking statistics. As such, these sources of uncertainty should be kept in mind or even used as error bars when assessing studies like this one.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…From studies based on the use of several reanalysis datasets with a single ETC-tracking algorithm, it is known that tracking results are also sensitive to the uncertainty in data (Hodges et al 2011). Data processing, like the interpolation of GCM outputs on a finer grid as in Long et al (2009), also influences tracking statistics. As such, these sources of uncertainty should be kept in mind or even used as error bars when assessing studies like this one.…”
Section: Discussionmentioning
confidence: 98%
“…Application of ETC tracking algorithms to RCM-produced datasets, however, introduces additional challenges. In order to investigate these challenges, we compare ETC tracking results of a simulation produced by the Canadian Regional Climate Model (CRCM) over North America at a 45-km resolution driven by ECMWF ERAInterim, with the results obtained directly from the driving Several studies have concentrated on comparing ETC statistics obtained from a tracking algorithm applied on both regional climate models outputs and global data (GCM or reanalysis) over the Atlantic (Jiang and Perrie 2007;Semmler et al 2008a, b;Woollings et al 2009;Long et al 2009), Europe (Lionello et al 2008) and over the Arctic (Shkolnik and Efimov 2013). Some of these studies are in fact sensitivity experiments where RCMs are driven by reanalyses in various contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The metric s BI is a measure of the growth rate of a baroclinic wave and is sometimes referred to as the eddy growth rate (Long et al 2009). Equation (1) can be rearranged and discretized as…”
Section: Low-level Baroclinicitymentioning
confidence: 99%
“…He et al 2013;Marciano et al 2015). Long et al (2009) have shown that an earlier version of the Canadian Regional Climate Model could improve the representation of intense cyclones with respect to its driving GCM. Among other interesting points, RCMs provide an improved description of the surface topography which, in the case of North America, is a decisive element in storm development (Brayshaw et al 2009).…”
Section: Introductionmentioning
confidence: 99%